2018
DOI: 10.3389/fpls.2018.01676
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of Barley Plant Productivity Through Regulation of Cytokinin Content by Reverse-Genetics Approaches

Abstract: Barley is one of the most important cereals, which is used for breweries, animal and human feeds. Genetic manipulation of plant hormone cytokinins may influence several physiological processes, besides others stress tolerance, root formation and crop yield. In planta, endogenous cytokinin status is finely regulated by the enzyme cytokinin dehydrogenase (EC 1.5.99.12; CKX), that irreversible degrades the side chain of adenine-derived isoprenoid cytokinins. Increasing grain yield by mean of manipulation of endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
55
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 72 publications
12
55
2
5
Order By: Relevance
“…A similar relationship between reduced expression of selected CKX family genes and cytokinin accumulation in reproductive organs has been observed in other species including A . thaliana (Bartrina et al, 2011), rice (Ashikari et al, 2005) and barley (Holubova et al, 2018), but detailed data are not comparable to our research in wheat.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…A similar relationship between reduced expression of selected CKX family genes and cytokinin accumulation in reproductive organs has been observed in other species including A . thaliana (Bartrina et al, 2011), rice (Ashikari et al, 2005) and barley (Holubova et al, 2018), but detailed data are not comparable to our research in wheat.…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, the authors observed no peaks and no differences in CKX activity at the particular stages of spike development, which is in agreement with homeostasis of the pool of isozymes in 7 DAP spikes of wheat, as suggested by us, which is independent of the level of silencing of TaCKX1 but is rather a consequence of co-regulation of expression of other TaCKX genes. A similar effect of increased grain yield, which was a consequence of higher spike and grain number, was obtained in barley with silenced by RNAi HvCKX1 , an orthologue of TaCKX1 (Zalewski et al, 2010; Zalewski et al, 2014; Holubova et al, 2018). The three CKs measured, cZ, tZ and iP, were differently regulated in earlier or later, but not precisely defined, stages of spike development (Holubova et al, 2018); therefore the results of CK contents are not comparable.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations